Narcissism - Smith, Laura L. (--For dummies., 2023)
"Narcissism For Dummies pulls back the curtain on a growing and misunderstood personality. This book digs into dimensions of narcissism, grandiosity, malignancy, and vulnerability, giving you the knowledge and perspective you need to identify narcissists in your life and set limits on unacceptable behavior. It also takes a look at how society plays a part in fostering narcissism, for example through social media. You'll walk away from Narcissism For Dummies with a clearer sense of the personality trait, as well as necessary coping mechanisms and tools to deal with the narcissists in your life. Deal with narcissistic parents, bosses, coworkers, relatives, romantic partners, and beyond. Discover tactics and exercises for identifying, disarming, and protecting yourself from narcissists. Set limits, establish healthy boundaries, and rebuild your self-confidence. Understand narcissistic personality in all its manifestations. Anyone whose life has been touched by narcissism will find this book helpful, whether you're coming to terms with a loved one's diagnosis, dealing with a narcissist in the workplace, or working to move forward after leaving a narcissistic relationship."--